Topical Metformin In Dermatology: A Narrative Review Of Efficacy And Formulation Approaches - Shofiatul Fajriyah; Fitria Wahyuningwulan; Lelly Winduhani; Fentyana Dwi Rilawati; Dyah Ayu Kusumaratni (MEDFARM: Jurnal Farmasi dan Kesehatan, 2025)
Metformin, a well-established first-line oral antidiabetic agent, has recently attracted interest in dermatology because of its anti-inflammatory, antioxidant, and regenerative properties. The skin, being vulnerable to aging and environmental damage, is a promising target for topical metformin therapy, although its clinical translation remains limited. This narrative review critically examines current evidence on topical metformin in dermatological applications and explores formulation approaches to optimize its cutaneous delivery. A thematic literature search was conducted in PubMed, Scopus, ScienceDirect, and Google Scholar for articles published between 2015 and 2025, focusing on studies of topical metformin for skin disorders. The final selection included 13 articles on wound healing, 5 on melasma, 1 on acne, 1 on psoriasis, and 1 on alopecia, all meeting predefined inclusion and exclusion criteria. Data from in vitro, in vivo, and clinical research were synthesized into three themes: pharmacological rationale, therapeutic efficacy, and formulation strategies. Promising results have been reported in melasma, acne, psoriasis, alopecia, and wound healing, where topical metformin has been shown to modulate melanogenesis, accelerate wound closure, reduce inflammatory cytokines, enhance hair regrowth, and support scar-free repair. Diverse formulations, including hydrogels, ethosomes, lipid nanoparticles, and niosomes, have been designed to improve skin penetration, drug retention, and therapeutic benefit while limiting systemic exposure